New model of Islamic art in public spaces - Zakariya, Khalilah; Zainal Abidin, Norzalifa; Hitam, Mizan; Mansor, Mazlina; Harun, Nor Zalina; Hassan, Haslina (2016)
The role of art in Islam has been noted to contribute towards the contemplative and inspirational relationship of a person with God as the Creator and the beauty of God’s creations. While the appreciation of Islamic arts has largely been applied in architecture, interior spaces, objects, and decorative patterns, there is a lack of research that explores the potentials of bringing Islamic art in the outdoor public space as a form of ‘public art’. In many published works, public art is defined as art in public places, which involves the artists, organizers, commissioned bodies and the community. While most Western approach on public art focus on enjoyment and the expression of the artists, the concept of Islamic art refers to artistic expressions that fundamentally derived from Tawhid or the contemplation of Divine Unity that has been portrayed formally in certain physical forms (calligraphy, geometric pattern, arabesque, non-figural representations). The aim of this research is to explore the potential manifestations of Islamic art in the public space to recommend how a new form of Islamic public art can be modelled. The objectives are: 1) To identify the attributes of Islamic arts in the public space through the concept of Islamic aesthetics; 2) To examine the process of developing Islamic art in the public space; 3) To assess the perceptions of Islamic art in the public space among the public. This research adopted a ‘design research’ approach, where designing is a way of researching – that is a way of producing knowledge. The methods comprised of three stages: 1) exploring and executing the graffiti as a new form of Islamic public art; 2) conducting a survey among 200 respondents; 3) conducting semi-structured interviews with 15 key informants from the art and religious background. The analysis revealed three key findings. First, the physical attributes and the placement of Islamic art in public spaces should conform to the Islamic ethical and spiritual values. Second, the message of the artwork should be easily understood by the public. Third, the process of executing the artwork should be a collaborative effort. The new model of Islamic art in public spaces from this research can guide the governing authority, artists, designers, the community and other researchers explore other forms of Islamic public art that are in line with the concept of Islamic values.